Role-Clarity and Boundaries for Trauma-Informed Teachers - Alex Shevrin Venet (Educational Considerations, 2019)
As they begin to implement trauma-informed practices in their classrooms, teachers should consider their role in the lives of students and how to maintain appropriate and safe boundaries with students. This essay explores the role of the teacher in supporting trauma-affected children and offers a frame of teacher as a facilitator of connection. It also offers ways to compassionately maintain boundaries with students while supporting their access to mental health care.
Keywords: trauma-informed; boundaries; trauma; role clarity